Faktor – Faktor Yang Mempengaruhi Tax Avoidance Pada Perusahaan FMCG di Indonesia - Musin, Abdurachman Menggala; Poetranto, Pradityo; Djohanputro, Bramantyo (JURNAL AKUNTANSI DAN AUDITING, 2021)
Indonesia's tax revenue realization tends to stagnate in the last five years indicating that taxpayers are performing tax evasion. The purpose of this research was analyzing the effect of Transfer Pricing on Tax Avoidance, to analyze the effect of Earnings Management on Tax Avoidance, to analyze the effect of Financial Leverage on Tax Avoidance, to analyze the effect of Firm Size on Tax Avoidance, to analyze the effect of Transfer Pricing, Earnings Management, Financial Leverage, and Firm Size on Tax Avoidance on FMCG companies listed on the Indonesia Stock Exchange from 2014 – 2019. A theoretical model with a hypothetical relationship is developed and tested with the help of multiple regression model analysis procedures through SPSS. This study uses a secondary data to collect data from FMCG companies listed on the Indonesia Stock Exchange for the period 2014-2019 as samples. The results of this study indicate that there is an effect of Transfer Pricing on Tax Avoidance, no effect of Earnings Management on Tax Avoidance, no effect of Financial Leverage on Tax Avoidance, an effect of Firm Size on Tax Avoidance, and effect of Transfer Pricing, Earnings Management, Financial Leverage, and Firm Size on Tax Avoidance on FMCG companies listed on the Indonesia Stock Exchange from 2014 – 2019.